香港課程改革成效之析評 An Analysis of the Effectiveness of Curriculum Reform in Hong Kong - 霍秉坤 Ping-Kwan Fok (Journal of Curriculum Studies, 2018)
2001年，香港課程發展議會發表《學會學習：課程發展路向》，開啟全面和影響深遠的課程改革。2014年，課程發展議會、香港考試及評核局、教育局檢視學會學習的實施後，發表《基礎教育課程指引─聚焦•深化•持續（小一至小六）》，以更新課程指引；新指引除回顧過去14年之實施成果外，亦補充舊課程指引之不足。本研究為回應教育局之小學課程指引，分為兩部分︰一、檢視課程改革 的成效；二、分析課程改革受局限之根本問題。簡言之，香港課程改革歷經十多年，獲得一定成效，但仍存在不少的隱憂。從課程改革進展報告、質素保證視學報告、學校周年報告和國際研究報告，皆顯示課程改革取得不錯的成果。然而，學生雖在國際評量中表現優異，但承受著極大的學習和考試壓力；教師雖在課程改革和 教學實踐中努力不懈、表現卓越，但仍面對沉重的工作壓力。香港課程改革要持續、有效地實施，亟需加強利害關係者之能量建構。 In 2001, Hong Kong started a comprehensive and massive impacted curriculum reform through introducing the Learning to Learn. In 2014, Curriculum Development Council, Hong Kong Examinations and Assessment Authority, and Education Bureau introduced the Basic Education Curriculum Guide: To Sustain, Deepen and Focus on Learning to Learn (Primary 1-6) to review the progress and achievements since the Learning to Learn curriculum reform. The Basic Education Curriculum Guide emphases for the ongoing curriculum renewal and updating over the past 14 years. This paper aims to review and discuss the Basic Education Curriculum Guide in 2014. The article is divided into two parts. First, it examines the effectiveness of curriculum reform. Second, it highlights the fundamental problem of curriculum reform in Hong Kong. In precise, even though the curriculum reform is more remarkable in Hong Kong over the last decade, it still challenged with a lot of impacts. The curriculum reform progress report, the quality assurance inspection report, annual school report and the international research report all show that the achievements of curriculum reform have been observed. However, students are pressed by course workload and examination pressure even their performance has been impressive in international assessments. Teachers always work hard in curriculum reform and teaching practice with exhibited outstanding performance. Nevertheless, the reform has led the intensification of teachers’ workload. Sustained and effective implementation of curriculum reform in Hong Kong depend on capacity building of difference stakeholders.